A Study in Late Preterm Babies for Early Neonatal Outcome - Sanjeet Kumar Tiwar; Nitish Kumar; Santosh Kumar; Renu Prabha (JCDR Research and Publications Pvt. Ltd., 2017)
Introduction: Infants born between 34 and 36 weeks gestation have an increased risk of neonatal morbidity requiring admission to a neonatal unit compared with those born at/or beyond 37 weeks gestation. Aim: To estimate the short term outcomes of late preterm babies in comparison with term babies and to study indication of caesarian section in late preterm deliveries. Materials and Methods: This prospective observational study was carried out at level II and level III Neonatal Care Unit and Obstetrics and Gynecology Department of North Bengal Medical College and Hospital. Total 7138 live babies were delivered during study period, out of them, 4891 babies were included in study group. Results: Total 919 late preterm were taken as cases and 3972 term neonates as control. Mean birth weight of term and late preterm neonates were 2.78 and 2.71kg respectively with standard deviation of 0.41 (p-value <0.01). Maternal age of term babies were 22.78 year with 3.81 standard deviation as against maternal age of late preterm were 23.03 with standard deviation 3.95 (p-value=0.0543). Among late preterm 120 (13.06%) developed respiratory distress as against 68 (1.71%) term neonates developed it during study period with a statistically significant p-value (p<0.01). 483 (52.56%) late preterm had jaundice while 1213 (30.54%) term babies developed it (p-value<0.001). Among all late preterm neonates 101 (10.99%) experienced one or more episodes of hypoglycemia while 57 (1.44%) term neonates experienced it (p-value<0.001). Hypothermia occurred in 73 (7.94%) late preterm neonates as against 69 (1.74%) term neonates (p-value<0.001). 39 (4.24%) late preterm experienced one or more episodes of apnoea as against 49 (1.23%) term babies (p-value<0.001). 166 (18.06%) late preterm babies had feeding problems but only 113 (2.84%) term babies had it (p-value<0.001). 90 (9.79%) term babies had confirmed sepsis while 70 (1.76%) term babies developed sepsis during study period (p-value<0.001). among all late preterm babies, 404 (43.96%) were delivered by caesarian section while rest 515 (56.04%) were delivered by spontaneous vaginal delivery. Among caesarian deliveries most common indication were foetal distress accounting for 12.8% of all deliveries followed by oligohydramnios (10.1%), meconium stained liquor (8.6%), IUGR (4%), Eclampsia (3.7%). Others less common are placental abruption, breech, CPD, uterine dehiscence. Mortality of late preterm was 7.29% (67) as against 47 (1.18%) terms. Conclusion: In contrast to very preterm infants, serious neonatal morbidity in (Late/Moderately Preterm) LMPT infants is uncommon. However, even modest increases in morbidity in this sizeable group exert very significant demands on neonatal service